2018
DOI: 10.1016/j.celrep.2018.03.034
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS9-Regulated Pericellular Matrix Dynamics Governs Focal Adhesion-Dependent Smooth Muscle Differentiation

Abstract: SUMMARYFocal adhesions anchor cells to extracellular matrix (ECM) and direct assembly of a pre-stressed actin cytoskeleton. They act as a cellular sensor and regulator, linking ECM to the nucleus. Here, we identify proteolytic turnover of the anti-adhesive proteoglycan versican as a requirement for maintenance of smooth muscle cell (SMC) focal adhesions. Using conditional deletion in mice, we show that ADAMTS9, a secreted metalloprotease, is required for myometrial activation during late gestation and for part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
3
37
0
Order By: Relevance
“…104 The properties of the PCM can be modulated by the activity of cell-surfaceassociated proteases or by altering the gene expression of PCM components in response to physiological and pathological stimuli. 105,106 Recently, proteomics studies identified more than 100 proteins at the cell surface and the PCM of tenocytes, illuminating the complexity of this ECM compartment. 103,107 Some of these PCM components, for which functions have been established, are discussed below.…”
Section: The Pcm Of Tendon-resident Cellsmentioning
confidence: 99%
“…104 The properties of the PCM can be modulated by the activity of cell-surfaceassociated proteases or by altering the gene expression of PCM components in response to physiological and pathological stimuli. 105,106 Recently, proteomics studies identified more than 100 proteins at the cell surface and the PCM of tenocytes, illuminating the complexity of this ECM compartment. 103,107 Some of these PCM components, for which functions have been established, are discussed below.…”
Section: The Pcm Of Tendon-resident Cellsmentioning
confidence: 99%
“…Versican and HA form a pericellular matrix in fibroblasts and vascular and myometrial smooth muscle cells (Evanko et al, 1999;Hattori et al, 2011;Mead et al, 2018) which is influential in determining cell phenotype. Specifically, HA, which is extruded from HAS2 complexes in the cell membrane, is decorated with versican and the complex is retained at the cell surface by binding CD44, HAS2 and other receptors (Evanko et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The versican-HA pericellular matrix has a well-established impact on different cells. It is anti-adhesive (Evanko et al, 1999;Mead et al, 2018), which may allow the Flk1+ cells to migrate and proliferate efficiently after their emergence at gastrulation. Another possible role of versican-HA is sequestration of vasculogenic factors such as VEGF-A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations